الضوابط القانونية لمعايير السياحة الحلال في القانون الليبي : (The Legal Controls for Halal Tourism Standards in Libyan Law ) - (Abdulbari Almabrouk Alfaytouri Amhimmid), عبد الباري المبروك الفيتوري امحمد; (Mohamed Ibrahim Negasi), محمد إبراهيم نقاسي; (Muhammad Laeba), محمد ليبا (At-Tajdid - Intellectual Refereed Journal, 2022)
The research seeks to clarify the position of the Libyan legislator on the concept of halal tourism and the extent to which its legitimate criteria are included in the Libyan tourism law and the related laws. This is because the term halal is not mentioned in laws related to tourism activity as this concept had only emerged in the last decade after considering the principles of Islamic law in tourism activity. Given the importance of tourism in supporting the national economy, there is a need to have the appropriate legal system for its requirements and highlight the lack of clear laws related to halal tourism standards and include them in the laws. The research used the inductive analytical approach to explore the extent to which those standards are legally included in the laws and regulations governing tourism activity and the legislation that is associated with it in Libya. The research concluded that the Libyan legislation does include the criteria of halal tourism in separate texts that are related to tourism activity but mentioning it as public activity, but this is still ambiguous. The term ‘conforming to Islamic law’ is used as an alternative to the term halal. The research recommended a legislative amendment that would explicitly indicate the term halal for the benefit of interested foreign tourists. The term is also to provide important requirements that do not exist in Libya related to tourism infrastructure, the most important of which are places dedicated to prayer in tourist areas, and above all, we ask God to ensure security and stability for Libya and all Muslim countries, the main factor of tourism activity. Keywords: Halal tourism, standards, controls, Libyan law